Ethnic Capital and Intergenerational Transmission of Educational Attainment - Agnieszka Postepska (Institute of Labor Economics (IZA), 2017)
This paper studies the role of ethnicity in the intergenerational transmission of educational attainment. Relying on heteroskedasticity to identify parameters in the presence of endogenous regressors, I revisit Borjas ethnic capital hypothesis. I find evidence that the OLS estimates of the effect of ethnic capital on intergenerational transmission of education are biased upwards due to the transfer of unobserved ability. I find that while the role of parental capital has declined over time, ethnic capital has a relatively constant effect on intergenerational transmission of educational attainment. I also find that only women benefit from the quality of the ethnic environment and that the intergenerational transfer of ethnic capital is most prevalent in communities with strong ties measured with endogamy rates.
Keywords: J15; J62; D1; Z1; 330; ethnic capital; human capital formation; intergenerational transmission